Secondary stress in contemporary British English: An overview - Quentin Dabouis (Anglophonia)
This paper presents a review of the literature on the nature and placement of secondary stress in English along with results from recent studies using dictionary data, which overall confirm what was known about secondary stress in English but bring a more fine-grained understanding of the phenomenon.